2019
DOI: 10.1177/2158244019865765
|View full text |Cite
|
Sign up to set email alerts
|

Social Trust, Pattern of Difference, and Subjective Well-Being

Abstract: Based on the pattern of difference in Chinese social trust, this study classifies the social trust into trust in family members, trust in acquaintances, and trust in strangers. Then, the correlational relationship between different types of social trust and subjective well-being is examined using the micro survey data in China. It is found that different types of social trust vary greatly in the correlation with subjective well-being. The main findings are as follows: (a) Trust in family members has no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Social trust is a mutual trust relationship established between individuals through interaction, communication and common awareness, which generally include two aspects: interpersonal trust and institutional trust [47]. Among them, interpersonal trust is mainly manifested as farmers' trust in their relatives and neighbors, which is formed through interactions in daily production and life with affinity, geopolitical relations and blood ties [48]. It can eliminate the risk of uncertainty in participation and decision [49,50].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…Social trust is a mutual trust relationship established between individuals through interaction, communication and common awareness, which generally include two aspects: interpersonal trust and institutional trust [47]. Among them, interpersonal trust is mainly manifested as farmers' trust in their relatives and neighbors, which is formed through interactions in daily production and life with affinity, geopolitical relations and blood ties [48]. It can eliminate the risk of uncertainty in participation and decision [49,50].…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The association remains robust when the likely mediators of social support and social capital are considered. In Confucian East Asia, the collectivistic culture promotes interdependence between significant others in homogeneous groups (Bai et al, 2019). In contrast, out-group trust fails to be associated consistently with SRH across the four countries.…”
Section: Resultsmentioning
confidence: 99%
“…In collectivistic societies, primary groups tend to govern the lives of individuals (Hofstede et al, 2010; Triandis, 1995). People give priority to group goals and communal bonds (Bai et al, 2019). As a result, particularistic ties based on a strong collective consciousness render social resources to be shared mostly within a group.…”
Section: Hypothesesmentioning
confidence: 99%
“…Poulin and Haase (2015) [ 27 ] found that trust increases well-being and higher trust predicted higher well-being. Bai et al (2019) [ 28 ] found that both trust in acquaintances and trust in strangers had a significant positive correlation with subjective well-being. Guo et al (2022) [ 29 ] found that all types of trust positively predicted well-being at the individual level, and the effects of trust on well-being were enhanced by individualism.…”
Section: Discussionmentioning
confidence: 99%